Enhancing Student Psychological Well-Being in Secondary Outdoor Education - Will Milner (Canadian Journal for New Scholars in Education)
This article reports on an examination of the perceptions of New Brunswick Outdoor Education (OE) teachers regarding the role and impact of various concepts of self and well-being in their high school OE classes. The researcher sought to analyze OE instructors’ observations and identify the pedagogy employed to enhance student well-being. A participatory action research (appreciate inquiry) approach was utilized. Data underwent narrative analysis and theme coding. While the emergent themes echoed the concepts in Deci & Ryan’s (2008) Self-Determination Theory (SDT), more significantly they demonstrated the importance of prioritizing certain SDT components over others throughout progression of the course. Findings also indicated that control over certain aspects of the course were necessary to manage to meet these prioritized needs, including relationships, selecting activities, creating a challenging environment, and the use of time within the course structure. Steps have already been untaken to actualize results within NB high schools.